2015
DOI: 10.1371/journal.ppat.1005228
|View full text |Cite
|
Sign up to set email alerts
|

Structure Analysis Uncovers a Highly Diverse but Structurally Conserved Effector Family in Phytopathogenic Fungi

Abstract: Phytopathogenic ascomycete fungi possess huge effector repertoires that are dominated by hundreds of sequence-unrelated small secreted proteins. The molecular function of these effectors and the evolutionary mechanisms that generate this tremendous number of singleton genes are largely unknown. To get a deeper understanding of fungal effectors, we determined by NMR spectroscopy the 3-dimensional structures of the Magnaporthe oryzae effectors AVR1-CO39 and AVR-Pia. Despite a lack of sequence similarity, both pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
335
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 222 publications
(354 citation statements)
references
References 93 publications
18
335
0
1
Order By: Relevance
“…M. oryzae isolates carrying the AVRPia-H3 allele are virulent on rice varieties carrying the Pia resistance locus and AVR-Pia-H3 does not interact in yeast two-hybrid (Y2H) assays with the C-terminal part of the rice NLR immune receptor RGA5 containing the RATX1 domain (RGA5 C-ter ). The NMR structure of AVR-Pia showed that both the F24 and T46 residues are surface exposed and suggested that the corresponding substitutions affect only AVR-Pia surface properties without major structural rearrangements (de Guillen et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…M. oryzae isolates carrying the AVRPia-H3 allele are virulent on rice varieties carrying the Pia resistance locus and AVR-Pia-H3 does not interact in yeast two-hybrid (Y2H) assays with the C-terminal part of the rice NLR immune receptor RGA5 containing the RATX1 domain (RGA5 C-ter ). The NMR structure of AVR-Pia showed that both the F24 and T46 residues are surface exposed and suggested that the corresponding substitutions affect only AVR-Pia surface properties without major structural rearrangements (de Guillen et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Although AVR-Pik, AVR-Pia, and AVR1-CO39 do not share sequence similarities, they share a highly similar three-dimensional structure characterized by a six b-sandwich fold also present in two other effectors: AvrPiz-t from M. oryzae and ToxB from the wheat pathogenic fungus Pyrenophora tritici repentis (Zhang et al, 2013;de Guillen et al, 2015;Maqbool et al, 2015;Nyarko et al, 2014). The corresponding, structurally related Magnaporthe Avr and ToxB effectors were termed MAX effectors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of effectors in fungal pathogen genomes are single genes and a rare few genes form small paralog families comprising up to three genes (de Guillen et al, 2015). These effectors do not share sequence homology with other effectors and also do not share any conserved motifs (de Guillen et al, 2015).…”
Section: Avrlm1mentioning
confidence: 99%
“…These effectors do not share sequence homology with other effectors and also do not share any conserved motifs (de Guillen et al, 2015). Ohm et al (2012) (Zhang et al, 2013) and Pyrenophora tritici-repentis (Sarma et al, 2005) that all share β-sandwich structures.…”
Section: Avrlm1mentioning
confidence: 99%